2016
DOI: 10.1111/avsc.12265
|View full text |Cite
|
Sign up to set email alerts
|

A higher‐level classification of the Pannonian and western Pontic steppe grasslands (Central and Eastern Europe)

Abstract: QuestionsWhat are the main floristic patterns in the Pannonian and western Pontic steppe grasslands? What are the diagnostic species of the major subdivisions of the class Festuco‐Brometea (temperate Euro‐Siberian dry and semi‐dry grasslands)?LocationCarpathian Basin (E Austria, SE Czech Republic, Slovakia, Hungary, Romania, Slovenia, N Croatia and N Serbia), Ukraine, S Poland and the Bryansk region of W Russia.MethodsWe applied a geographically stratified resampling to a large set of relevés containing at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 32 publications
2
51
1
2
Order By: Relevance
“…Intuitively, one might think that higher numbers of species per group might result in more accurate classification. If so, it would be straightforward to use diagnostic species of individual vegetation types, defined using statistical indices such as the phi coefficient (Chytrý et al 2002, Tichý & Chytrý 2006 or constancy ratio (e.g., Willner et al, 2017) directly for discriminating among vegetation types in the expert system. We used such an approach as one variant of our tests ("From data") and found that it did not perform very well regarding the number of correctly classified plots.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intuitively, one might think that higher numbers of species per group might result in more accurate classification. If so, it would be straightforward to use diagnostic species of individual vegetation types, defined using statistical indices such as the phi coefficient (Chytrý et al 2002, Tichý & Chytrý 2006 or constancy ratio (e.g., Willner et al, 2017) directly for discriminating among vegetation types in the expert system. We used such an approach as one variant of our tests ("From data") and found that it did not perform very well regarding the number of correctly classified plots.…”
Section: Discussionmentioning
confidence: 99%
“…Each vegetation type has one (and just one) discriminating species group, but single species can occur in more than one discriminating species group. The discriminating species group of a particular vegetation type is usually different from the diagnostic species group (e.g., Chytrý et al 2002;Willner et al, 2017) of that type, although a significant proportion of species is shared between these groups. Besides species, other taxa such as subspecies or species aggregates can be included in these groups, but for simplicity, all of them are called "species" throughout this paper.…”
Section: Description Of the Grimp Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Нові синтаксони встановлювали шляхом порівняння фітоценонів один з одним та з описаними раніше синтаксонами (Korotchenko, Didukh, 1997;Krasova, Smetana, 1999;Moysiyenko et al, 2005;Korotchenko et al, 2009а, b;Vynokurov, 2014а, 2016Kolomiychuk, Vynokurov, 2016;Willner et al, 2017;etc.). Для порівняння використано 174 описи, результати відображені в синоптичній таблиці (табл.…”
Section: матеріали та методиunclassified